Identifying the enemy : civilian participation in armed conflict - Crawford, Emily (Writer on international law) (Oxford : Oxford University Press, 2015)
Civilians are increasingly playing crucial roles in the conduct of military operations. This book looks at different forms of civilian participation in armed conflict, examining the pressure this disruptive practice places on the traditional laws of war.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on August 18, 2015).
Keywords: Humanitarian law; Civilians in war